2018 IEEE 59th Annual Symposium on Foundations of Computer Science (FOCS) 2018
DOI: 10.1109/focs.2018.00060
|View full text |Cite
|
Sign up to set email alerts
|

EPTAS for Max Clique on Disks and Unit Balls

Abstract: We propose a polynomial-time algorithm which takes as input a finite set of points of R 3 and computes, up to arbitrary precision, a maximum subset with diameter at most 1. More precisely, we give the first randomized EPTAS and deterministic PTAS for Maximum Clique in unit ball graphs. Our approximation algorithm also works on disk graphs with arbitrary radii, in the plane.Almost three decades ago, an elegant polynomial-time algorithm was found for Maximum Clique on unit disk graphs [Clark, Colbourn, Johnson; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…We answer in Section 4 the 2-dimensional version of the question asked by Bonamy et al [4]: We present a polynomial time algorithm for computing a maximum clique in a geometric superclass of interval graphs and unit disk graphs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We answer in Section 4 the 2-dimensional version of the question asked by Bonamy et al [4]: We present a polynomial time algorithm for computing a maximum clique in a geometric superclass of interval graphs and unit disk graphs.…”
Section: Resultsmentioning
confidence: 99%
“…However in 2017, Bonnet et al, found a subexponential algorithm and a quasi polynomial time approximation scheme (QPTAS) for computing a maximum clique on disk graphs [5]. The following year, Bonamy et al extended the result to unit ball graphs, and gave a randomised EPTAS for both settings [4]. The current state-of-the-art about the complexity of computing a maximum clique in d-ball graphs is summarised in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is accomplished by casting the maximum weight clique problem as an integer program and designing a local search method that avoids entrapment in local optima thanks to a couple of perturbations. Likewise, the authors in [76] propose a polynomial time algorithm so as to discover the maximum clique in unit ball graphs.…”
Section: E Special Algorithms For the Clique Problemmentioning
confidence: 99%